2008
DOI: 10.1158/1078-0432.ccr-07-4782
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Potent Humoral Immune Responses to Autoantigens Are Associated with Tumor Destruction and Favorable Clinical Outcomes without Autoimmunity

Abstract: Purpose: The therapeutic importance of immune responses against single versus multiple antigens is poorly understood. There also remains insufficient understanding whether responses to one subset of antigens are more significant than another. Autoantibodies are frequent in cancer patients. They can pose no biological significance or lead to debilitating paraneoplastic syndromes. Autoreactivity has been associated with clinical benefits, but the magnitude necessary for meaningful results is unknown. Autologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Gogas and colleagues (44) showed that the preventive efficacy of IFN-α in high-risk melanoma patients was significantly correlated with an increase in serum levels of antithyroid, antinuclear, anti-DNA, and anticardiolipin autoantibodies. Although those authors regard the humoral response as a prognostic marker, it is possible that the survival benefit was gained by immune targeting of biologically significant antigens shared by normal and tumor cells (45). This is possibly the case for the significant correlation we found between survival and the increase in the antibody level against livin.…”
Section: Discussionmentioning
confidence: 82%
“…Gogas and colleagues (44) showed that the preventive efficacy of IFN-α in high-risk melanoma patients was significantly correlated with an increase in serum levels of antithyroid, antinuclear, anti-DNA, and anticardiolipin autoantibodies. Although those authors regard the humoral response as a prognostic marker, it is possible that the survival benefit was gained by immune targeting of biologically significant antigens shared by normal and tumor cells (45). This is possibly the case for the significant correlation we found between survival and the increase in the antibody level against livin.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, cell-based cancer vaccines can be used to elicit broader Ab responses that closely resemble those associated with naturally occurring TIL-Bs. For example, in melanoma and prostate cancer patients receiving cell-based vaccines expressing GM-CSF, the development of autoantibodies to self-antigens was associated with favorable clinical responses (91)(92)(93). It is less clear how best to enhance the immunoregulatory and Ag presentation functions of TILBs.…”
Section: Discussionmentioning
confidence: 99%
“…Combined treatment with lower doses of CT plus GM-CSF secreting whole cancer cell vaccines might therefore overcome immune tolerance and induce anti-tumor immune responses [180]. It is important to note that immune responses against multiple antigens are associated with efficient tumor destruction [181].…”
Section: Radiotherapy Combined With Immune Activatorsmentioning
confidence: 99%